Inovasi Teknologi Madya pada Masyarakat Adat Kasepuhan Ciptagelar - Ryan Aldi Nugraha (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
The barometer of prosperity in a country is seen from the self-sufficiency of its people. How the community is able to explore resources to meet common needs, while preserving the values that are rooted in society. The phenomenon of traditional villages that have deep-rooted philosophical values as a form of local wisdom is increasingly being abandoned by people who consider them ancient, irrelevant for future life, because prosperity in today's world is closely correlated with the use of technology. One of the characteristics of prosperity in a country can be seen from the aspect of community self-reliance. How can people be a ble to explore resources to meet common needs, preserve values rooted in society and deal with the flow of modernization. Ciptagelar is a traditional village that has become one of the characteristics of prosperity by creating new innovations, processing renewable energy sources through the use of intermediate technology to answer common needs. Â Â This writing uses a qualitative method with a case study approach. The location of the writing is in Kasepuhan Ciptagelar, Sirnaresmi Village, Cisolok District, Sukabumi Regency. Data collection uses observation, documentation and in-depth interviews with customary chiefs, electricity holders, traditional elders, and indigenous peoples who benefit from the development of intermediate technology. The validity of the data is done by triangulating the source, because at this writing the data obtained will be collected to be matched and to know the truth. Data analysis techniques consist of reduction, presentation and conclusion. The findings of the writing conclude that the strong reason for the Kasepuhan Ciptagelar indigenous people to innovate in developing intermediate technology is due to the need for electricity supply for households, and is strengthened by the statement of Abah Encup Sucipta (the previous customary chairman) so that it is not eroded by the times. The process of developing a power generator water turbine as an intermediate technology by utilizing river water resources in Cicemet, Cibadak and Sukamulya. The benefits of this intermediate technology are felt by indigenous peoples in addition to being able to meet household needs as well as lower monthly costs than PLN